Corporate philanthropy toward the community and organisational commitment in the fitness sector. (14th November 2011) - Lubinsky, Marla; Doherty, Alison; Kerwin, Shannon
This study examined the influence of corporate philanthropy (CP) toward the community (specifically organisation and employee giving and volunteering) on three dimensions of organisational commitment among a sample of head office staff (N = 91) of a large fitness organisation. Corporate involvement and corporate support for employee volunteering were found to be positively associated with affective commitment, and negatively associated with continuance commitment. Neither type of CP was associated with normative commitment. The findings extend our understanding of the nature and influence of CP, and have implications for its development as a strategic practice in the fitness sector.